PENENTUAN KOEFISIEN SERAPAN KAYU BANGKIRAI (SHOREA LAEVIFOLIA) DAN PERBANDINGANNYA TERHADAP TIMBAL (Pb) SEBAGAI DINDING RUANG RADIOLOGI DIAGNOSTIK - Japeri Japeri; Heri Sutanto; Choirul Anam (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Shield utilization is very important to protect employee and people from radiation. Therefore, the rules are made that one of them is to regulate construction design of diagnostic radiology room which meet radiation protection standart. Indonesia has natural resources which potential to be radiation shield material. The research has been done to determine absorption coeffcicient of bangkirai (Shorea laevifolia) and its comparison with Pb as wall of diagnostic radiology room. X-ray absorption between bangkirai and Pb as the following : Voltage, current and time of X-ray mobile were setted in 81 kV and 32 mAs, distance between focus and object was 100 cm, Multi Purpose Detector (MPD) placed under object, area of irradiation field opened in 5 cm x 5 cm, central beam placed in the center of objects appropriately and then expotion was conducted for untreated bangkirai with (Pb) and treated bangkirai which heated in 100°C for 60 minutes repeteadly according to variation of determined thickness material, finally expotion was conducted for each thickness for three times so that average value obtained and it was repetead until absorption coefficient value of this material obtained. Result of X-ray absorption on bangkirai tests showed that absorption coefficient () effective for untreated bangkirai and treated bangkirai is 0,029/mm and 0,027/mm, respectively. Equality result showed that unheated bangkirai with 1,3 mm Pb is equivalent with 254 mm untreated bangkirai, while heated bangkirai with 1,3 mm Pb is equivalent with 273 mm treated bangkirai. To reach 2 mm of Pb, untreated bangkirai and treated bangkirai were used with thickness off 391 mm and 420 mm, respectively.Keywords : X-ray mobile, Multi Purpose Detector (MPD), Pb, Bangkirai, Absorption Coefficient ()